What renders financial advisors less treacherous? On commissions and reciprocity - Vera Popova (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
An advisor is supposed to recommend a financial product in the best interest of her client. However, the best product for the client may not always be the product yielding the highest commission (paid by product providers) to the advisor. Do advisors nevertheless provide truthful advice? If not, will a voluntary or obligatory payment by a client induce more truthful advice? According to the results, only the voluntary payment reduces the conflict of interest faced by advisors.
Keywords: C91; D82; D03; L15; M52; 330; financial advisors; moral hazard; reciprocity; experiments